Application of three-dimensional Raman imaging to determination of the relationship between cellular localization of diesel exhaust particles and the toxicity. (13th June 2022) - Ou, Langying; Honda, Akiko; Miyasaka, Natsuko; Akaji, Sakiko; Omori, Issei; Ishikawa, Raga; Li, Yinpeng; Ueda, Kayo; Takano, Hirohisa
Abstract: A diesel exhaust particle (DEP) is a type of particulate matter that is easily produced from combustion in a diesel power engine. It has been reported that DEPs can cause short- and long-term health problems. This is because DEPs are complex mixtures that are highly inhalable through the airways due to their small particle size. However, the relationship between intracellular localization of DEPs after their deposition in the lungs and the subsequent biological responses remains to be clarified. This is due to difficulties in distinguishing particles that are inside the cells from those that are outside. In this study, A549 human lung epithelial cells were exposed to DEPs at concentrations of 0, 25, 75, or 200 µg/mL for different periods, after that particles in the A549 cells were analyzed by three-dimensional (3D) images obtained from a Raman microscope. The cytotoxic effects of DEPs on the A549 cells were investigated by measuring cell viability, the levels of intracellular reactive oxygen species (ROS) and cell death. The Raman microscopy revealed that the particles invaded the A549 cells, and at a concentration of 200 µg/mL, they markedly decreased cell viability, increased intracellular ROS production, triggered late apoptosis/necrosis and induced nuclear damage. These results suggest that intracellular DEPs exposed at a high concentration may be highly toxic and can impair the viability of A549 cells. Furthermore, the 3D images from the Raman microscopy can be used to evaluate intracellular particle dynamics.